1981
DOI: 10.1111/j.1365-2265.1981.tb00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Various Degrees of Hypothyroidism Among Patients of a General Medical Department

Abstract: We have measured basal thyrotropin (TSH) in 945 consecutive patients of a general medical department. Additional thyroid tests were carried out in patients with elevated TSH. Thirty patients (3.1%) had subclinical hypothyroidism, i.e. an elevated TSH with no clinical signs and with a normal free thyroxine index. A cause was found in only fifteen of these thirty patients. Thirteen additional patients (1.37%) had mild or overt primary hypothyroidism, three of which were already diagnosed. This prevalence is thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 9 publications
1
16
0
1
Order By: Relevance
“…[11][12][13][14] In this study, the majority of Saudis and non-Saudis were found to be relatively young at the time of diagnosis. Although this observation is not surprising in non-Saudis, the majority of whom, being expatriate employees, are expected to be young, it is intriguing in Saudis.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] In this study, the majority of Saudis and non-Saudis were found to be relatively young at the time of diagnosis. Although this observation is not surprising in non-Saudis, the majority of whom, being expatriate employees, are expected to be young, it is intriguing in Saudis.…”
Section: Discussionmentioning
confidence: 99%
“…Across studies, the prevalence of SCH (like overt hypothyroidism) is consistently higher in women than in men (Table 2) (17)(18)(19)(20)(21)23,25,27,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). In the Whickham study, the prevalence of SCH in women was 7.5%, nearly three times the prevalence in men (2.8%) (19).…”
Section: Sexmentioning
confidence: 97%
“…In the early Whickham study in the United Kingdom (N = 2779), 5.0% of individuals older than 18 years were classified as having SCH, defined as TSH > 6 mIU/l in the absence of symptoms of hypothyroidism (19). In 1981, Riniker et al (20) reported a prevalence of SCH of 3.1% among 945 patients in a general medical department in Switzerland. In this study, SCH was defined for asymptomatic individuals as TSH > 6 mIU/l in combination with FT4 > 51 nmol/l (20).…”
Section: Historical Prevalence Of Schmentioning
confidence: 99%
See 2 more Smart Citations